(untitled) (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2022)
Islamic boarding schools are non-profit entities and have a very important role in the preparation of financial statements, until now Islamic boarding schools in Indonesia still use simple financial statements. Therefore, BI cooperates with IAI to issue Islamic boarding school accounting guidelines (PAP) and PSAK 45. The method used in this research is qualitative with a descriptive approach. This study aims to determine and analyze the recording of financial statements in Islamic boarding schools in Jambi in accordance with Islamic boarding school accounting guidelines and PSAK 45. In the results of the study, the components of Islamic boarding schools accounting guidelines consist of statements of financial position, reports on changes in net assets, cash flow statements, notes on financial statements. whereas in PSAK 45, statements of financial position, activity reports, cash flow statements, and notes to financial statements, until now Islamic boarding schools only use simple financial reports because they do not understand well about Islamic boarding school accounting guidelines, due to lack of knowledge and information about accounting guidelines pesantren and PSAK 45.